It seems like the details of what p and q <em>are </em>in this context aren't all that important; it's the logical structure of the statement "p⇒q" we need to look at. We read that logical statement as "p implies q," where p is our <em>hypothesis</em> and q is our <em>conclusion</em>. When we take the converse of a logical statement, we reverse the hypothesis and the conclusion. In this case, <em>p </em>wouldn't imply <em>q</em>, but <em>q </em>would imply <em>p</em> in the converse of p⇒q. We'd write this statement as:
q⇒p
✡ Answer: 27 ✡
- - Why?
(0, * 1) + (1 * 27) = 27
✡Hope this helps✡
Answer:
no 1/4 is bigger than 3/8
Step-by-step explanation:
Inverse of F(x) is f(x) = x+6
Explanation:
Given :
F(x) = x-6
In mathematics, an inverse function (or anti-function) is a function that reverses another function: f y i.e., f(x) = y if and only if g(y) = x.
So, according to question
F(x)= x-6
Now we will solve the right hand side of the equation
x=F(x)+6
So inverse of F(x) is f(x) = x+6